EFFECTS ANALYSIS OF LEVERAGE, PROFITABILITY, COMPANY SIZE, AUDIT QUALITY, AND TAX AVOIDANCE ON PROPENSITY EARNINGS MANAGEMENT WITH INDEPENDENT COMMISSIONERS AS MODERATING VARIABLES IN MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE 2021-2024 PERIOD - Marihot PH Simarmata; Erlina; Khaira Amalia Fachrudin (CV. Radja Publika, 2025)
This study aims to analyze the effect of leverage, profitability, firm size, audit quality, and tax avoidance on the Propensity earnings management, with independent commissioners as a moderating variable in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This research employs a quantitative approach using a census method, in which all mining companies listed on the IDX during the study period, totaling 54 firms, were included as the research sample. The data were analyzed using panel data regression with the Random Effect Model (REM), which was selected based on the Chow test and the Hausman test. The earnings management was measured using discretionary accruals based on the Kasznik (1999) model, which represents the degree of a firm’s tendency to engage/Propensity in earnings management practices. The results indicate that leverage and tax avoidance have a positive effect on Propensity earnings management, suggesting an increase in the propensity (tendency) of management to engage in earnings management practices. Conversely, profitability, firm size, and audit quality have a negative effect on Propensity earnings management, indicating that firms with better financial performance and stronger monitoring mechanisms tend to exhibit a lower of Propensity earnings management. Furthermore, independent commissioners are found to weaken the relationship between leverage, profitability, firm size, audit quality, and Propensity earnings management; however, they do not moderate the relationship between tax avoidance and Propensity earnings management. This study confirms that financial factors and corporate governance mechanisms play an important role in influencing earnings management practices in the mining sector. The presence of independent commissioners is proven to be an effective monitoring mechanism in reducing the Propensity earnings management, except in the context of tax avoidance practices. These findings provide important implications for investors, regulators, and management in evaluating the quality of financial reporting and the effectiveness of good corporate governance.